A qualitative study on women’s breast cancer diagnosis disclosure preferences and disclosure experiences in a middle-income country - Frema Osei-Tutu; Merri Iddrisu; Gladys Dzansi; Tabitha Gyenewaa Quaidoo; Ofosu-Poku Rasheed; Prince Appiah Yeboah (International Journal of Africa Nursing Sciences, 2023)
With the increasing cancer incidence in Ghana especially breast cancer among women, its diagnosis and prognosis present enormous fear and worry for women and their families. Thus, breaking the news of breast cancer diagnosis to patients presents enormous difficulty to healthcare professionals. Aim: This study sought to explore the preferences of people living with breast cancer regarding the disclosure of their diagnosis. Methods: The study used an exploratory-descriptive qualitative design to recruit and interviewed 17 women diagnosed with breast cancer and receiving treatment in a National Radiotherapy and Nuclear Medicine Center of a major Teaching Hospital in Ghana. Data were analyzed using Braun and Clarke’s 2006 thematic analysis approach. Findings: Two major themes, six subthemes, and five sub-subthemes were generated from the data. The study found that patients preferred detailed information on the stage of their cancer diagnosis, treatment options, and the lifestyle necessary to enhance their health. The participants preferred that the news of their diagnosis be broken to them gradually in the form of a conversation with consolatory gestures, without any hidden information. From the study, clinicians do not follow any specific systematic method in the disclosure process, clinicians used a conversation approach involving consolation, encouragement, comic words, and pampering mostly in disclosing cancer diagnosis which was found relieving.In conclusion, People living with breast cancer prefer full gradual disclosure of diagnosis in a conducive environment in the presence of loved ones in a humane manner.